We need kernel interposition over the network dataplane - Sadok, Hugo; Zhao, Zhipeng; Choung, Valerie; Atre, Nirav; Berger, Daniel S.; C. Hoe, James; Panda, Aurojit; Sherry, Justine (HotOS, 2021)
Kernel-bypass networking, which allows applications to circumvent the kernel and interface directly with NIC hardware, is one of the main tools for improving application network performance. However, allowing applications to circumvent the kernel makes it impossible to use tools (e.g., tcpdump) or impose policies (e.g., QoS and filters) that need to interpose on traffic sent by different applications running on a host. This makes maintainability and manageability a challenge for kernel-bypass applications. In response, we propose Kernel On-Path Interposition (KOPI), in which traditional kernel data-plane functionality is retained but implemented in a fully programmable SmartNIC. We hypothesize that KOPI can support the same tools and policies as the kernel stack while retaining the performance benefits of kernel bypass.